Omni-directional bands in multilayer structure containing exponentially graded materials - Thapa K.B.; Pandey P.C.; Singh S.K.; Ojha S.P. (My University, 2025)
The omni-directional reflection (ODR) in a one-dimensional multilayered structure containing exponentially graded material is studied theoretically using the transfer matrix method. We propose a periodic multiplayer structure containing alternate layers of the exponentially graded refractive index and layers of constant refractive index. The reflectance for TE- and TM-modes of the structure are studied for different angles of incidence. We obtained two ODR bands, one in the visible and the other in the infrared region for both polarizations. The behavior of the ODR band in the infrared region is different from the usual Bragg ODR band in the visible region. The width of the ODR band for the TM-mode is larger that for the TE-mode in the wavelength range 850 nm-1050 nm. Such a structure with a large ODR band may be useful in the design of a broad infrared reflector.